AL-ISLAH FI FIKRI MUHAMMED ABDUH - RASOOL, OTHMAN AHMED RASOOL (Fırat Üniveristesi, 2018)
Bu tez çalışması, etimolojik ve terim anlamını barındırmanın yanında, Muhammed Abduh'un Kur'an-ı Kerim âyetlerini nasıl anlayıp yorumladığını ihtiva eder. Ayrıca ona göre doğru olan ve olmayan davranışın ne olduğu, doğru olmayan davranışın ümmeti fesada götürüp götürmeyeceğini içerir. Bunların yanında Muhammed Abduh'un doğumu, hayatı, ilmi ve sosyal hayatı, Ezher Üniversitesindeki hocalarını, öğrencilerini, eserlerini, metodunu ve Cemaleddin Efgânî ile olan dostluğunu barındırır. Çalışmamızda beyan ettiğimiz üzere, Muhammed Abduh'a ait olup günümüze yansıyan akidevi anlayış ve görüşleri; etimolojik, terimsel ve siyasal anlayış açısından; dinî, eğitsel ve fikri açıdan ele alıp değerlendirdik. Aynı şekilde bu çalışmada, Muhammed Abduh'un fikirleri, ilmi ve ameli hayattaki ıslah fikirlerini, özellikle Mısır'dan Beyrut'a sürgün edilişi ve Cemaleddin Efgânî ile olan dostluğu beyan edilmiştir. Ayrıca memleketine döndükten sonra; yenilenme, hüküm, fetva, yargı, ilmi, dini tecdit ve toplumdaki ahlak anlayışı konusundaki görüşlerinde meydana gelen değişimler ele elınmıştır. Bu çalışmada, günümüzde köklü bir akidevi anlayışa sahip Muhammed Abduh'a ait olan ve ona yakışmayan fikirleri onun metoduyla açıklamaya çalıştık.

This research deals with the definition of the language reform and its terminology? and how to explain the verses of The Holy Quran in the reform As understood by Mohammed Abduh? and also to show that what is good work and what is the corrupt work? the corruption work permits to do corrupting by the nation? and the life of Abduh from his birth and his scientific background and his practical? social and activity life and his writings? styles and his ideas. Also showed the side of the reform creed by Mohammed Abduh in the reform concept and the reform in modern time? reform understanding and the reform vision of Mohammed Abduh in linguistics and politics also he stood up for religious and educational reform in his thought. This resarch is an expression of the thought of Muhammed Abduh? and also to show his reformist view in his practical and scientific life? especially after his exile from Egypt to Beirut and his friendship with Jamal Al Din Al Afghani. And after returning to his country? his vision and his reformist ideology was changed specially in his political reform and his decision? advisory opinions? judicial? religious reform? scientific? and his moral that related to his social activities. This research had written on the method of Muhammed Abduh to prove his live with the ideas that are not suitable with his religious faith and keeping the credo of his Islamic religious which synchronous with modern times.
Muhammed Abduh'un Islah düşüncesi
Keywords: Din